Deficiency of electron transport chain in human skeletal muscle mitochondria in type 2 diabetes mellitus and obesity - Ritov, Vladimir B; Menshikova, Elizabeth V; Azuma, Koichiro; Wood, Richard; Toledo, Frederico G. S; Goodpaster, Bret H; Ruderman, Neil B; Kelley, David E (American journal of physiology: endocrinology and metabolism, 2010)
1 Department of Medicine, University of Pittsburgh School of Medicine, Pittsburgh, Pennsylvania; and 2 Diabetes Research Unit, Boston Medical Center, Boston University School of Medicine, Boston, Massachusetts Submitted 15 May 2009 ; accepted in final form 27 October 2009 Insulin resistance in skeletal muscle in obesity and T2DM is associated with reduced muscle oxidative capacity, reduced expression in nuclear genes responsible for oxidative metabolism, and reduced activity of mitochondrial electron transport chain. The presented study was undertaken to analyze mitochondrial content and mitochondrial enzyme profile in skeletal muscle of sedentary lean individuals and to compare that with our previous data on obese or obese T2DM group. Frozen skeletal muscle biopsies obtained from lean volunteers were used to estimate cardiolipin content, mtDNA (markers of mitochondrial mass), NADH oxidase activity of mitochondrial electron transport chain (ETC), and activity of citrate synthase and β-hydroxyacyl-CoA dehydrogenase (β-HAD), key enzymes of TCA cycle and β-oxidation pathway, respectively. Frozen biopsies collected from obese or T2DM individuals in our previous studies were used to estimate activity of β-HAD. The obtained data were complemented by data from our previous studies and statistically analyzed to compare mitochondrial content and mitochondrial enzyme profile in lean, obese, or T2DM cohort. The total activity of NADH oxidase was reduced significantly in obese or T2DM subjects. The cardiolipin content for lean or obese group was similar, and although for T2DM group cardiolipin showed a tendency to decline, it was statistically insignificant. The total activity of citrate synthase for lean and T2DM group was similar; however, it was increased significantly in the obese group. Activity of β-HAD and mtDNA content was similar for all three groups. We conclude that the total activity of NADH oxidase in biopsy for lean group is significantly higher than corresponding activity for obese or T2DM cohort. The specific activity of NADH oxidase (per mg cardiolipin) and NADH oxidase/citrate synthase and NADH oxidase/β-HAD ratios are reduced two- to threefold in both T2DM and obesity. insulin resistance; β-oxidation; cardiolipin; reduced nicotinamide adenine dinucleotide/nicotinamide adenine dinucleotide ratio; trichloroacetic acid cycle Address for reprint requests and other correspondence: V. B. Ritov, Univ. of Pittsburgh, School of Medicine, Div. of Endocrinology and Metabolism, 810N MUH, 3459 5th Ave., Pittsburgh, PA 15213 (e-mail: ritovatpitt.edu ).